PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS 3D PADA MATERI SISTEM KOMPUTER DI KELAS X DKV DI SMKN 2 PADANG PANJANG - Septa Della; Thomson Mary; Bernediv Nurdin (LPPM Politeknik Pratama Kendal, 2025)
This study aims to develop a three-dimensional (3D)-based learning media for the Computer System material for grade X DKV students at SMKN 2 Padang Panjang. The background of this research is the low interest and understanding of students in the subject, caused by the limited variety of teaching methods and the lack of interactive media use. In today’s digital era, integrating technology into learning is essential to improve the effectiveness of the teaching and learning process. The method used is Research and Development (R&D) with the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The media was developed using Assemblr Edu and Canva applications, validated by two media experts and two subject matter experts, and tested for practicality by one teacher and 25 students. The validation results showed a validity score of 96.30% from media experts and 81.67% from material experts, both categorized as very valid. The practicality test obtained a score of 86.98% from the teacher and 85.63% from students, both classified as very practical. The developed media presents the learning content in a visual and interactive 3D format, enhancing student engagement and comprehension. In conclusion, the 3D learning media developed in this study is feasible and effective for use in classroom learning. It is expected to serve as an innovative solution in supporting technology-based learning, particularly in vocational education settings